ANALISIS PENGARUH DAYA TARIK IKLAN DAN ELECTRONIC WORD OF MOUTH (e-WOM) TERHADAP MINAT PENGGUNAAN JASA DI LKP SINAR ABADI SINGKAWANG - Erik Sudarso; Gian Chung; Venny Adhita Octaviani (FOKUS : Publikasi Ilmiah untuk Mahasiswa, Staf Pengajar dan Alumni Universitas Kapuas Sintang., 2026)
In the era of globalization, mastery of foreign languages has become an essential aspect in facilitating various cross-border activities in the fields of education, business, and social interaction. Along with the rapid economic growth of China, the demand for Mandarin language proficiency has significantly increased worldwide, including in Indonesia. Singkawang City, known for its strong interest in learning Mandarin, has experienced a notable rise in the number of language training institutions, one of which is the Lembaga Kursus dan Pelatihan (LKP) Sinar Abadi. This study aims to analyze the influence of Advertising Attractiveness and Electronic Word of Mouth (e-WOM) on the Interest in Using Services at LKP Sinar Abadi Singkawang. The research employed a quantitative approach, with data collected through questionnaires distributed to 100 respondents who were familiar with or had used the institution’s services. The collected data were analyzed using multiple linear regression analysis to examine the relationship between independent and dependent variables. The findings reveal that both Advertising Attractiveness and Electronic Word of Mouth have a positive and significant effect on the Interest in Using Services at LKP Sinar Abadi Singkawang. These results highlight the importance of implementing appealing promotional strategies and effective digital communication to enhance potential students’ interest in enrolling in language courses.